The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25081785
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Hsp90 N-Terminal Dynamics: Structural and Molecular Insights into the Therapeutic Activities of Anticancer Inhibitors Radicicol (RD) and Radicicol Derivative (NVP-YUA922)

Abstract: Heat shock protein 90 (Hsp90) is a crucial component in carcinogenesis and serves as a molecular chaperone that facilitates protein maturation whilst protecting cells against temperature-induced stress. The function of Hsp90 is highly dependent on adenosine triphosphate (ATP) binding to the N-terminal domain of the protein. Thus, inhibition through displacement of ATP by means of competitive binding with a suitable organic molecule is considered an attractive topic in cancer research. Radicicol (RD) and its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Hitherto, among the 19 N-terminal targeted HSP90 inhibitors that made it to the clinical trials, none has been approved by FDA. This is because of harmful health effects such as the heat shock response (HSR) induction [ 63 ]. Figure 2 shows 2D structures of some of the failed N-terminal HSP90 inhibitors at the clinical trials.…”
Section: Development Of Heat Shock Protein 90 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hitherto, among the 19 N-terminal targeted HSP90 inhibitors that made it to the clinical trials, none has been approved by FDA. This is because of harmful health effects such as the heat shock response (HSR) induction [ 63 ]. Figure 2 shows 2D structures of some of the failed N-terminal HSP90 inhibitors at the clinical trials.…”
Section: Development Of Heat Shock Protein 90 Inhibitorsmentioning
confidence: 99%
“…Over the years, researchers explored the use of natural products in the development of HSP90 inhibitors. Delmotte and Delmotte-Plaquee discovered radicicol (RD) as an extract from monosporium border and used it as a macrocyclic lactone antibiotic [ 63 , 67 ]. In 1998, Schulte et al identified radicicol as a competitive HSP90 inhibitor to geldanamycin (GA) [ 68 ].…”
Section: Development Of Heat Shock Protein 90 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that there are prospects for both radamine and compound 7.7 towards targeting parasite Grp94, which may result in antiplasmodial activity. Preliminary studies identified NVP-AUY922, also known as luminespib ( Figure 7 ), a resorcinylic isoxazole amine that binds and inhibits Hsp90 with a higher affinity than radamide [ 165 ]. The binding affinity for luminesbip to PfGrp94 was 10-fold higher compared to the cytosolic PfHsp90 and HSPC2 [ 81 ].…”
Section: P Falciparum Hsp90 As Drug Targetsmentioning
confidence: 99%